THE DEVELOPMENT OF COMIC STRIP MEDIA TO TEACH READING SKILL IN MA ASSALAM JAMBEWANGI - Andrea nora Santika; Ahmad Saifudin; Siti Rofi'ah (IKIP Siliwangi, 2023)
This research aims to describe the process and results the development of comic strip media for teaching reading skills in explanatory text material. The research subjects were 10 students of class XI MA Assalam jambewangi. The development procedure refers to the ADDIE model. Observation techniques, questionnaires and observations were used as information gathering in the preliminary study. Meanwhile, to determine the feasibility of comic strip products, researchers used a questionnaire instrument given to content and media experts. Then a student response questionnaire was conducted to determine the level of student satisfaction with the media. According to the content expert's assessment, a score of 88% was obtained in the very good category. From media experts, a score of 98% was obtained which was classified in the very Good category. In addition, the results of the student response questionnaire also scored 79% in the good category. Based on the overall assessment, the development of comic strip learning media on giving and asking for information themed explanatory text material for class XI students was declared valid and suitable for use teaching and learning activities in the School.